Personalized Orthopedics Contributions and Applications of Biomedical Engineering - Canciglieri Junior, Osiris; Trajanovic, Miroslav D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers the most important topics in the field of personalized orthopedics. It starts with the 3D geometry of the bones, focusing on the problem of reverse engineering of the bones. It also shows the application of a 3D geometric model of bone for the design of personalized implants and prostheses. This book covers the application of additive technologies in personalized orthopedics as well as prediction, simulation and optimization in personalized orthopedics. Its content provides the necessary knowledge for the transition from classical to personalized orthopedics. The authors present an original method for reverse bone engineering$1 (Bthe Method of Anatomical Features (MAF). This method is unique as it enables the reconstruction of the original geometry and topology of the bone, even when only data on its part are available. The application of this method is shown on the examples of human long bones, mandible and hip bone reconstruction. This book contains a review of several real cases of personalized implants. It gives several examples of prostheses for the design of which a 3D model of bones was used, as well as other patient data on the basis of which personalized prostheses were designed.s
Personalized Orthopedics -- Reverse Engineering of Human Bones -- Personalized Implants -- Personalized Prothesis -- Additive Manufacturing and Personalized Materials -- Prediction, Optimization and Monitoring.
Keywords: Engineering design; Bones; Physiology; Engineering Design; Bone Physiology; Biomedical engineering; Orthopedics; Personalized medicine